Growth rates in a European eel Anguilla anguilla (L., 1758) population show a complex relationship with temperature over a seven-decade otolith biochronology. (20th January 2021) - Vaughan, Louise; Brophy, Deirdre; O'Toole, Ciar; Graham, Conor; Ó Maoiléidigh, Niall; Poole, Russell
Abstract: Environmental and habitat change can have profound and complex impacts on fish. We examined an unexploited population of European eel ( Anguilla anguilla) from a West of Ireland catchment. The population is long-lived and slow-growing compared to many other European eel populations. Von Bertalanffy growth curves showed decadal changes, with a trend towards larger K, and t0 values in both males and females and a smaller L ∞ in females. A growth biochronology spanning seven decades (1950s–2010s) was constructed using otolith annual increment measurements. We found evidence of high variability in growth over the course of the time series. A decrease in growth occurred after the early 2000s, potentially driven by habitat and climatic changes. Growth was negatively correlated with early spring and winter temperatures, providing strong evidence that the length of the growing season impacts eel growth. Growth was also positively correlated with summer temperatures and the number of days that exceeded 16˚C (GSL16˚C). The response to temperature was age-dependent; at age one the positive relationship with GSL16˚C was most pronounced and the negative relationship with winter temperatures was not evident. This study demonstrates the impact of climate change and highlights the complexities of eel growth strategies in a changing environment.